2022
DOI: 10.1039/d2tc01281b
|View full text |Cite
|
Sign up to set email alerts
|

Phase control of sputter-grown large-area MoTe2 films by preferential sublimation of Te: amorphous, 1T′ and 2H phases

Abstract: The crystallization mechanism of sputter-deposited amorphous Mo–Te film is revealed enabling the large-area growth of 2D materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…However, in fact, the present authors have observed similar amorphous-layered crystal transition in a MoTe 2 thin film, which possesses the same stoichiometric ratio as GeTe 2 . 20 It should be noted that in a previous work on MoTe 2 , the structural similarities between amorphous and crystalline MoTe 2 films were invoked to partially explain the crystallization process. Recently, the detailed structure of glassy GeTe 2 bulk has been revealed, where tetrahedral GeTe 4 and trigonal GeTe 3 units as well as Te oligomers were found to coexist.…”
Section: Structural Determinationmentioning
confidence: 97%
“…However, in fact, the present authors have observed similar amorphous-layered crystal transition in a MoTe 2 thin film, which possesses the same stoichiometric ratio as GeTe 2 . 20 It should be noted that in a previous work on MoTe 2 , the structural similarities between amorphous and crystalline MoTe 2 films were invoked to partially explain the crystallization process. Recently, the detailed structure of glassy GeTe 2 bulk has been revealed, where tetrahedral GeTe 4 and trigonal GeTe 3 units as well as Te oligomers were found to coexist.…”
Section: Structural Determinationmentioning
confidence: 97%
“…[5] Among these compounds, MoTe 2 exhibits polymorphic phase transitions within hexagonal (2H) and monoclinic (1T′) or orthorhombic (T d ) crystal structures; switching between these phases can also be realized by the application of external stimuli such as temperature, electric-field or pressure. [3,[6][7][8][9][10][11] As a result, MoTe 2 has been extensively studied as a switching layer in nextgeneration non-volatile memories (NVMs), such as resistive random access memory (ReRAM) and phase-change random access memory (PCRAM), due to the large changes in electrical properties ranging from metallic to semiconducting accessable by switching between phases. Zhang et al reported an electric-field-induced structural transition from a 2H semiconducting to a distorted transient [11,15,[29][30][31] the T c and T m values of NbTe 4 were defined by the onset temperature of crystallization and melting peaks in this study; B) XRD curves of NbTe 4 thin films annealed at various temperatures; C) cross-sectional TEM image of 350 °C annealed NbTe 4 thin film; D) zoomed in image of the white-box area in (C); E) the FFT pattern taken from the area of (D).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this technique has been applied for the large-area growth of TMDs such as MoTe 2 and MoS 2 . [11,15,16] Interestingly, as-deposited sputtered TMDs are typically amorphous; the layered crystalline structure can be formed by post-annealing at elevated temperature. Such an amorphousto-crystalline phase transition is often observed for chalcogenidebased phase-change materials (PCMs) such as Ge 2 Sb 2 Te 5 (GST) used in rewritable optical discs and PCRAM devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[49][50][51][52][53][54][55][56][57] 1T 0 (or 1T) phase group VIB TMDs, for example, in which one chalcogen layer is offset relative to the other to produce an M-centered octahedral, have shown an excellent ability to minimize resistance in electrical devices. [58][59][60] Producing the semi-metallic 1T 0 phase (or the metallic 1T phase) simply by intercalating with alkali metals, 61,62 subjecting the material to mechanical stresses, [63][64][65] modulating the electrical field, 66,67 and so on is difficult. The use of phase transitions and phase-selective synthesis is in high demand.…”
Section: Introductionmentioning
confidence: 99%